"I often have to explain to school staff what she needs". School experiences of non-autistic siblings growing up with an autistic brother or sister. (October 2022) - Pavlopoulou, Georgia; Burns, Clare; Cleghorn, Rosie; Skyrla, Theodora; Avnon, Julia
Abstract: Background: Recent autism research has evidenced a shift from psychological outcomes to contextualised approaches to understanding the varying needs of non autistic siblings of autistic children across different systems. Yet, there is limited research exploring the lived experiences of siblings in their school context. Methods: First, a group of school aged sibling advisors worked with the first author to codesign research aims, methods and dissemination practices around the topic of the school experiences of siblings who grow up with an autistic brother or sister in the UK. Then, 28 school-aged siblings of autistic children completed adapted photo-elicitation interviews, to discuss their school experiences. A background questionnaire was also administered to their parents and carers. Results: Thematic analysis was employed. The master themes included: (i) Impact of home experiences in schoolwork, including limited personal time and sleep disruptions (ii) Siblings' school interactions impact on overall school experience, including a wide range of both typical and difficult experiences such as school day disruptions, (iii) Varied perceived levels of support and understanding, including emotional and/or educational support by family members and a sense of connectedness with peers and teachers who are autistic themselves or connected to someone with a diagnosis of autism. Implications: The results underline the ways home experiences can have an impact on school life of siblings, the positive contribution of the autistic school staff and/or staff who have an autistic family member and the need for an organisational culture of inclusivity and widespread acceptance and awareness around issues of neurodiversity. Our findings suggest several implications for school psychologists in core functions of the educational psychologists' role including training, consultation, assessment, and whole school support. Data availability statement: The datasets generated for this study are not readily available because they include sensitive data (photos of siblings' houses, family members, personal objects, and school timetables). Requests to access the datasets should be directed to corresponding author. Highlights: The findings of the current study point to several positive experiences by interacting with autistic people. This message is important for parents, siblings and autistic people themselves. Our results suggest that siblings do not automatically experience difficulties in adjusting at school, but may be at increased risk for experiencing difficulties related to lack of autism awareness and acceptance. Home-to-school transition after half term may pose challenges considering that some siblings may have experienced a difficult time at home due to their increased responsibilities.